Penerapan Metode Bernyanyi untuk Melatih Daya Ingat Anak Usia 4-5 Tahun di TK Khadijah 21 Tegaldlimo Banyuwangi Tahun Ajaran 2024/2025 - Octa Viana, Ria (Universitas Islam Zainul Hasan Genggong, 2025)
The singing method has many benefits, including developing children's confidence, having strong thinking, always having good feelings and moods. The results of a similar study presented in his writing that the singing method can increase children's confidence. Thus, the method of singing in training memory in children. Memory is the ability to recall data that has been stored in memory when needed. Basically, according to Jensen, memory is something that forms human identity and distinguishes humans from other creatures. Memory for children is the ability of the child's brain to capture, store, and regenerate information that has been obtained or experienced by the child. The memory in this study is that children can remember memorizing the Hadith given by the teacher. This research uses qualitative The type of research used is field research, which is research conducted in the field, involving the local community. Field research usually creates extensive field records which are then coded and analyzed in a variety of ways. Khadijah 21 Kindergarten is an Islamic-based early childhood education institution, which is located in Krajan hamlet, Kedunggebang Village, Tegaldimo District, Banyuwangi Regency. Khadijah 21 Kindergarten, especially in group A, applies the singing method in the learning process to train memory, Considering that learning activities are activities that tend to be monotonous if there is no singing for students, Khadijah 21 Kindergarten teachers innovate in providing learning that can make students feel cheerful, happy, excited and easily understand the material, namely using the singing method to train children's memory, If the material is given by the singing method and given repeatedly, the material will be recorded in the child's brain and moreover the child can easily memoriz.